STRATEGI PRACTICE REHEARSAL PAIRS DALAM PEMBELAJARAN DRAMA MUSIKAL BAGI SISWA SEKOLAH DASAR DI SANGGAR TARI GIRI KESWARA KEDIRI - Chintya Anggun Yonada; Dilla Octavianingrum; Permata Heldisari (Universitas Hamzanwadi, 2026)
Musical drama is an art learning model that integrates three fields: drama, dance, and music. Sanggar Tari Giri Keswara Kediri teaches musical drama to elementary school students. It requires a teaching method that accommodates various skills according to the characteristics of elementary students who are beginning to build interactions with their peers. The Practice Rehearsal Pairs strategy can improve student participation in paired activities. This study aims to identify and describe the implementation of a learning strategy in musical drama lessons for elementary school students at Sanggar Tari Giri Keswara Kediri. The research method used is descriptive qualitative, with subjects consisting of musical drama instructors, students, and the management of Sanggar Tari Giri Keswara Kediri. The object of this research is the use of the Practice Rehearsal Pairs strategy in musical drama learning. Data collection techniques include observation, interviews, and documentation, with validation using source and technique triangulation. Data analysis involves data organization, comprehensive reading, coding, theme identification, and data interpretation. The results show that the Practice Rehearsal Pairs strategy is applied in musical drama learning through vocal, expression, dance, and singing exercises. This strategy enhances students' social interaction and their integrated skills in drama, dance, and music.